MENUMBUHKAN KARAKTER TANGGUNG JAWAB SISWA SDN 064990 MELALUI IMPLEMENTASI PROYEK KELAS BERBASIS KERJA - Darinda Sofia Tanjung; Sihombing, Yesicha R; Valentino Tarigan; Dodo Renaldi Tampubolon; Emeilia Anastasia Sebayang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve elementary school students' responsibility character through the implementation of a Classroom Work-Based Project at SDN 064990. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles involving planning, action, observation, and reflection. The participants were 30 elementary school students. Data were collected through observations, interviews, documentation, and responsibility-character assessment sheets. Data were analyzed using descriptive qualitative and quantitative techniques based on the percentage of responsibility character achievement. The findings revealed that the implementation of the Classroom Work-Based Project successfully enhanced students' responsibility character. The level of responsibility increased from 61.83% in the preliminary condition to 74.67% in Cycle I and reached 88.91% in Cycle II, which was categorized as excellent. Students also demonstrated better discipline, independence, environmental awareness, and collaborative skills in completing classroom responsibilities. Therefore, the Classroom Work-Based Project can be considered an effective instructional strategy for strengthening character education in elementary schools.